Enhancing primary care services for diverse sexual and gender minority populations: a developmental study protocol. Issue 2 (25th February 2020) - Willging, Cathleen; Kano, Miria; Green, Amy Elizabeth; Sturm, Robert; Sklar, Marisa; Davies, Sonnie; Eckstrand, Kristen
Abstract : Introduction: Compared with heterosexual, cisgender populations, sexual and gender minority (SGM) people are more likely to suffer from serious health conditions and insufficient access to health services. Primary care is at the frontlines of healthcare delivery; yet, few clinics have resources or mechanisms in place to meet SGM patient needs. This developmental study protocol focuses on reducing health disparities among SGM patients by identifying, adapting and developing SGM practice guidelines/recommendations and implementation strategies for primary care clinics in urban and rural New Mexico. Using input from patients, healthcare advocates and providers, and researchers, the study will pilot a practice parameter and implementation toolkit to promote SGM-specific cultural competence at multiple service delivery levels. Methods and analysis: We will recruit providers/staff from four Federally Qualified Health Centers (FQHCs) serving ethnically and geographically diverse communities. Incorporating the Implementation of Change Model and an intersectionality perspective, data collection includes a systematic review of SGM-specific practice guidelines/recommendations, focus groups and semistructured interviews, quantitative surveys and the Nominal Group Technique (NGT) with providers/staff. We will categorise guidelines/recommendations identified through the review by shared elements, use iterative processes of open and focused coding to analyse qualitative data from focus groups, interviews and the NGT, and apply descriptive statistics to assess survey data. Findings will provide the foundation for the toolkit. Focus groups with SGM patients will yield supplemental information for toolkit refinement. To investigate changes in primary care contexts following the toolkit's pilot, we will undertake systematic walkthroughs and document review at the FQHCs, analysing these data qualitatively to examine SGM inclusiveness. The structured data-informed Plan-Do-Study-Act method will enable further revision of the toolkit. Finally, focus groups, interviews and quantitative surveys with providers/staff will highlight changes made in the FQHCs to address SGM patient needs, barriers to sustainment of changes, satisfaction, acceptability, usability and feasibility of the toolkit. Ethics and dissemination: The study has been reviewed and approved by the Pacific Institute for Research and Evaluation Institutional Review Board. Informed consent will be obtained from all participants before their involvement in research activities begins. Study results will be actively disseminated through peer-reviewed journals, conference presentations, social media and the internet, and community/stakeholder engagement activities.